Olaparib and α-specific PI3K inhibitor alpelisib for patients with epithelial ovarian cancer: a dose-escalation and dose-expansion phase 1b trial. Issue 4 (April 2019) - Konstantinopoulos, Panagiotis A; Barry, William T; Birrer, Michael; Westin, Shannon N; Cadoo, Karen A; Shapiro, Geoffrey I; Mayer, Erica L; O'Cearbhaill, Roisin E; Coleman, Robert L; Kochupurakkal, Bose; Whalen, Christin; Curtis, Jennifer; et al.
Summary: Background: Based on preclinical work, we found that combination of poly (ADP-ribose) polymerase (PARP) inhibitors with drugs that inhibit the homologous recombination repair (HRR) pathway (such as PI3K inhibitors) might sensitise HRR-proficient epithelial ovarian cancers to PARP inhibitors. We aimed to assess the safety and identify the recommended phase 2 dose of the PARP inhibitor olaparib in combination with the PI3K inhibitor alpelisib in patients with epithelial ovarian cancer and in patients with breast cancer. Methods: In this multicentre, open-label, phase 1b trial following a 3 + 3 dose-escalation design, we recruited patients aged 18 years or older with the following key eligibility criteria: confirmed diagnosis of either recurrent ovarian, fallopian tube, or primary peritoneal cancer of high-grade serous histology; confirmed diagnosis of either recurrent ovarian, fallopian tube, or primary peritoneal cancer of any histology with known germline BRCA mutations; confirmed diagnosis of recurrent breast cancer of triple-negative histology; or confirmed diagnosis of recurrent breast cancer of any histology with known germline BRCA mutations. Additional patients with epithelial ovarian cancer were enrolled in a dose-expansion cohort. Four dose levels were planned: the starting dose level of alpelisib 250 mg once a day plus olaparib 100 mg twice a day (dose level 0); alpelisib 250 mg once a day plus olaparib 200 mg twice a day (dose level 1); alpelisib 300 mg once a day plus olaparib 200 mg twice a day (dose level 2); and alpelisib 200 mg once a day plus olaparib 200 mg twice a day (dose level 3). Both drugs were administered orally, in tablet formulation. The primary objective was to identify the maximum tolerated dose and the recommended phase 2 dose of the combination of alpelisib and olaparib for patients with epithelial ovarian cancer and patients with breast cancer. Analyses included all patients who received at least one dose of the study drugs. The trial is active, but closed to enrolment; follow-up for patients who completed treatment is ongoing. This trial is registered withClinicalTrials.gov, numberNCT01623349 . Findings: Between Oct 3, 2014, and Dec 21, 2016, we enrolled 34 patients (28 in the dose-escalation cohort and six in the dose-expansion cohort); two in the dose-escalation cohort were ineligible at the day of scheduled study initiation. Maximum tolerated dose and recommended phase 2 dose were identified as alpelisib 200 mg once a day plus olaparib 200 mg twice a day (dose level 3). Considering all dose levels, the most common treatment-related grade 3–4 adverse events were hyperglycaemia (five [16%] of 32 patients), nausea (three [9%]), and increased alanine aminotransferase concentrations (three [9%]). No treatment-related deaths occurred. Dose-limiting toxic effects included hyperglycaemia and fever with decreased neutrophil count. Of the 28 patients with epithelial ovarian cancer, ten (36%) achieved a partial response and 14 (50%) had stable disease according to Response Evaluation Criteria in Solid Tumors 1.1. Interpretation: Combining alpelisib and olaparib is feasible with no unexpected toxic effects. The observed activity provides preliminary clinical evidence of synergism between olaparib and alpelisib, particularly in epithelial ovarian cancer, and warrants further investigation. Funding: Ovarian Cancer Dream Team (Stand Up To Cancer, Ovarian Cancer Research Alliance, National Ovarian Cancer Coalition), Breast Cancer Research Foundation, Novartis.